Solar battery charging station and torque sensor based electrically assisted tricycle - Faraz, T.; Azad, AKM Abdul Malek (© 2012 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 2nd IEEE Global Humanitarian Technology Conference, GHTC 2012; Seattle, WA; United States; 21 October 2012 through 24 October 2012 [© 2012 IEEE ] The conference paper's definite version is available at: http://doi.org/10.1109/GHTC.2012.62